Manual of Multi-Storey Timber Construction : principles - construction - examples - Kaufmann, Hermann, ....-; Krötsch, Stefan, ....-; Winter, Stefan, ....- (Munich : Detail Business Information GmbH, 2022)
The renewable construction material timber has become the epitome of sustainability - and thus, a promise for the future of construction. Since timber, nearly without limitation, is suitable for use in the construction of multi-storey buildings, a stronly increasing demand can be observed. In parallel, the need for well-founded and constructive knowledge is also on the rise - among those responsible for planning and among clients. Modern timber construction is disengaging from classical categorisations of timber frame construction, solid timber construction and others. It also supports sensible combinations of different construction types within a project. This opens up completely new opportunities for architectural approaches to timber construction. The publication focuses on multi-storey timber construction. It conveys the essential expert knowledge on new methods of systematisation and construction - from design to prefabrication and assembly on-site - and presents a selection of examples from practice. This approach to the topic contributes to the reciprocal understanding among all project partners involved in an integrated planning construction process. The manual provides readers with the necessary expertise to convincingly promote and implement modern timber construction.
Keywords: Houtconstructie -- architectuur